Estimated cardiac output and cardiovascular profile score in fetuses with high cardiac output lesions. (25th December 2012) - Statile, C. J.; Cnota, J. F.; Gomien, S.; Divanovic, A.; Crombleholme, T.; Michelfelder, E.
Abstract: Objective: High cardiac output lesions are associated with an increased risk of fetal death, largely as a result of cardiac failure and hydrops fetalis. The cardiovascular profile score (CVPS) has been used to characterize cardiovascular wellbeing, and has been linked to fetal outcomes in other conditions. We aimed to test the hypothesis that elevated combined cardiac output (CCO) in fetuses with high output lesions may be associated with worsening cardiovascular status, as evidenced by a lower CVPS . Methods: A retrospective review was performed of fetuses with high cardiac output lesions that underwent echocardiography between July 2006 and November 2010. Diagnoses included sacrococcygeal teratoma, placental chorioangioma and vein of Galen aneurysm. Fetal echocardiographic evaluation included assessment of CVPS, as well as Doppler/two‐dimensional estimation of CCO, indexed to estimated fetal weight (CCOi). The relationship between CCO and CVPS was assessed . Results: A total of 35 fetuses were studied: 27 had sacrococcygeal teratoma, seven had chorioangioma and one had vein of Galen aneurysm. There was a significant inverse relationship between mean logCCOi and CVPS (r 2  = 0.48, P = 0.008). Of 31 patients with clinical outcome data, 10 experienced either in‐utero demise or intervention; 80% of these fetuses had a CVPS of < 8 . Conclusions: There is an inverse relationship between CCO and CVPS in the fetus with high cardiac output lesions. As a measure of fetal cardiovascular wellbeing in this population, the CVPS may be a useful tool for stratifying risk and for selection for intervention in these fetuses .